Political communication strategies through Facebook and TikTok: Xavier Hervas case.: Political communication strategies through Facebook and TikTok: Xavier Hervas case - Calva-Jiménez, Jessenia Mishelle; León-Alberca, Tatiana Betzabé; Calva-Cabrera, Ketty Daniela (Quórum Académico, 2023)
The media ecosystem is changing as a result of technological advances, which has meant that political actors and their communication teams are rethinking their ways of communicating with the electorate. This research analyzes the use of Facebook and TikTok by Xavier Hervas, a presidential candidate in the General Elections of Ecuador in 2021. The initial data of the research contextualize the digital consumption situation in Ecuador, considering the effects of Covid-19. Through a qualitative approach methodology, the communication strategies and discourse of the participant were studied. A quantitative approach was applied to understand engagement. Upon completion of the analysis, data on the content with the highest reception and the techniques that  ontributed to its positioning were obtained.